Generalized method to estimate value of urban assets for natural disaster risk assessment at the macro scale - Suwathep, T; Lim, W; Iseri, Y; Kanae, S (J-STAGE, 2015)
Natural disasters can have a damaging effect on human society. To understand the magnitude of risk of a natural disaster at the macro scale, basic socioeconomic parameters such as population or gross domestic product (GDP) are often used as proxies to evaluate value of specific asset classes (e.g., urban assets, agricultural land, etc.). However, such information is not always available and it becomes a challenge to perform cost-benefit analysis of tailored strategies to protect an asset class from natural disaster risk. Recent studies showed the prospects of relating GDP and population to produced capital representing urban assets. However, the methods used in earlier studies are unclear and resulted in different outcomes that need further clarification and generalization. This study aims to demonstrate the potential of developing a more generalized method to characterize the relation between produced capital and basic socioeconomic parameters at the global scale. We include purchasing power parity (PPP) into the country GDP and produced capital data, respectively. We develop a more generalized method that incorporates the uncertainty range to quantify the produced capital. This is an improvement from previous studies. The new approach might be useful for macro scale risk assessment within the context of climate change.